2014
DOI: 10.4067/s0718-58392014000300001
|View full text |Cite
|
Sign up to set email alerts
|

Response of root characteristics and yield in peanut under terminal drought condition

Abstract: Drought at pod filling reduces growth, yield, and seed quality of peanut (Arachis hypogaea L.) Great root system can reduce yield loss under water stress. There is a lack of information on root traits for peanut genotypes and the relationship between rooting traits and peanut yield under terminal drought. The pot experiments were conducted at Khon Kaen University, Thailand, in 2004Thailand, in -2005Thailand, in and 2005Thailand, in -2006. A randomized complete block design was used with two factorials set-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…The RI for YT was higher than 47 % for all genotypes, with cultivar IAC Tatu ST being the most sensitive to water deficit conditions with an RI of 68 % (Table 2). Similar results were reported by Junjittakarn et al (2014), who observed that water deficits at the end of the peanut growth cycle affected Positive RI values were observed for all evaluated parameters for most genotypes, which indicates that water deficits caused physiological changes in plants, particularly on the parameters PP and YT, which were reduced ( Table 2). The production component most affected by water deficit was the number of pods, although in the BRS Havana cultivar and inbred line DW (kg ha yield-related characteristics, such as pod DW and the harvest index.…”
Section: Resultssupporting
confidence: 77%
“…The RI for YT was higher than 47 % for all genotypes, with cultivar IAC Tatu ST being the most sensitive to water deficit conditions with an RI of 68 % (Table 2). Similar results were reported by Junjittakarn et al (2014), who observed that water deficits at the end of the peanut growth cycle affected Positive RI values were observed for all evaluated parameters for most genotypes, which indicates that water deficits caused physiological changes in plants, particularly on the parameters PP and YT, which were reduced ( Table 2). The production component most affected by water deficit was the number of pods, although in the BRS Havana cultivar and inbred line DW (kg ha yield-related characteristics, such as pod DW and the harvest index.…”
Section: Resultssupporting
confidence: 77%
“…The initial plant morphological response to drought stress is the growth rate. Reduced growth may be an adaptive response to abiotic stress (Junjittakarn et al, 2014). Plant growth is one parameter in the drought-sensitive morphological processes caused by the decreased turgor pressure during drought stress (Misra et al, 2002;Inostroza et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to Junjittakarn et al (2014) the peanut crop extracts 75% of the total N in the fruits while the other 25% is distributed between the leaves and branches. Also according to these authors, the high N extraction for the fruits and the availability of this nutrient favors the yield between the pod and the grains.…”
Section: Peanut Cultivars Submitted To Irrigation Levels and Nitrogenmentioning
confidence: 99%